Implementation Management Arabic Incentive Program in Markaz al-Lughah al-‘Arabiyah Annuqayah Madura - Fudhaili, Achmad; Muawanah, Elyatul; Khairiyah, Faiqatul (Kalimatuna: Journal of Arabic Research, 2022)
This study discusses the management of the implementation of the Arabic language course program which was carried out intensively at the Markaz al-Lughah al-Arabiyah (MLA) Pondok Pesantren Annuqayah Madura. This research uses descriptive qualitative research method. Data was collected by observation, interviews, and documentation. The research instrument consisted of the researchers themselves, interview sheets, observation guidelines, recording devices, and writing instruments. Data analysis in this study was carried out by interactive qualitative analysis consisting of data reduction, presentation, and conclusion drawing. The results of this study indicate that: The management of the implementation of the Arabic language course at MLA based on bi'ah lughawiyah consists of learning achievement targets, teaching systems, compacting activities, class classification, textbooks, and daily evaluations. The results of this study indicate that the compulsory environmental management-based language course makes it easier for students to master the language well and quickly.